Activity of gemmogenesis in regenerated plants of hazelnut cv. ‘Akademyk Yablokov’ and antibiotic therapy for elimination of bacterial contamination in vitro - T. A. Krasinskaya (Труды по прикладной ботанике, генетике и селекции)
Background. The problem of obtaining certified planting material with biotechnological methods is important for expanding commercial and homestead plantations of hazelnut cultivars in Belarus. Materials and methods. Regenerated plants of cv. ‘Akademyk Yablokov’, representing the genus Corylus L., were a model object for studying in vitro morphogenesis and effectiveness of antibiotics against bacterial contamination, so that a protocol could be developed to obtain healthy planting material of hazelnut cultivars. The plants produced during this study were included in the duplicate ex situ collection of nut crops preserved in vitro in the active growth state. Results. Single exposure to the antibiotic kanamycin monosulfate at a concentration of 100 mg/L during antibiotic therapy in the stage of in vitro micropropagation eliminated bacterial infection in 83.3% of regenerated plants, and twofold exposure in 100%. Further cultivation revealed its phytotoxic aftereffect manifested in the form of necrosis on most of the regenerated plants and a decrease in the activity of gemmogenesis and growth. Neither single nor twofold exposure to cefotaxime sodium salt at a concentration of 90 mg/L caused elimination of bacterial infection, but gemmogenesis and regenerated plant growth retained their activity during subsequent cultivation on antibiotic-free media. The best development parameters were observed on a modified Murashige–Skoog medium with 6 mg/L 6-BA, 0.01 mg/L IBA, and 0.1 mg/L GA3 (average number of shoots: 2.2; number of microcuttings: 2.3), and a modified DKW medium with 6 mg/L 6-BA, 0.01 mg/L IBA, and 0.1 mg/L GA3 (average number of shoots: 2.05; microcuttings: 2.9). The use of zeatin as a cytokinin to stimulate adventitious morphogenesis or activate the growth of axillary meristems at a concentration of 5 or 6 mg/L was not as effective as 6-BA.